2019
DOI: 10.1097/ftd.0000000000000637
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Pediatric Dosing Recommendations and Treatment Management of Antiretroviral Drugs Using Therapeutic Drug Monitoring Data in Children Living With HIV

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 111 publications
1
15
0
1
Order By: Relevance
“…This study found that ARV drugs improves the quality of life of Indonesian children with HIV/AIDS, which is a condition consistent with some previous studies [17][18][19]. ARV therapy suppresses viral replication and reduces viral load in blood thereby boosting immune system [20], and has been shown to improve physical functioning of children with HIV/AIDS [21].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study found that ARV drugs improves the quality of life of Indonesian children with HIV/AIDS, which is a condition consistent with some previous studies [17][18][19]. ARV therapy suppresses viral replication and reduces viral load in blood thereby boosting immune system [20], and has been shown to improve physical functioning of children with HIV/AIDS [21].…”
Section: Discussionsupporting
confidence: 90%
“…The caregiver stigma measurement obtained a value of 21.7 ± 2.06, with a median value of 22 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). There was no signi cant effect between caregiver stigma on the quality of life of Indonesian children with HIV/AIDS (β = 0.064; p = 0.548), with value of each subscale as follows: physical function (β = 0.023; p = 0.845), emotional function (β = -0.066; p = 0.608), social function (β = 0.007; p = 0.957), and school function (β = 0.097; p = 0.418).…”
Section: Characteristics Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in a review of all of the literature to date on ARV dosing for individuals with a median or mean age ≤ 18 under the current international guidelines for ARV dosage (Waalewijn et al, 2019), it is noted that pediatric ARV dosing is often based on small samples, and simplified to provide practical information across general contexts of disease. Yet there is high interindividual variation in the pharmacokinetic parameters of pediatric ARVs, indicating a potential risk of under-or overdosing, and therefore more close monitoring of ARV dosing, and related factors, is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Dose recommendations for paediatric ART are often based on small studies, but paediatric ART dose optimization is becoming increasingly important in drug development. 15 There are, however, still many knowledge gaps concerning ART in children receiving concomitant TB treatment, and vice versa. 16 First-line treatment of drug-susceptible TB in children consists of isoniazid, rifampicin, pyrazinamide and ethambutol for 2 months, followed by isoniazid and rifampicin for 4 months.…”
Section: Introductionmentioning
confidence: 99%